An Unusual Presentation of a Posterior Mediastinal Schwannoma Associated with Traumatic Hemothorax - Ruchi Amin; Brett H. Waibel (Case Reports in Surgery)
Schwannomas of the thoracic cavity are typically an asymptomatic, benign neurogenic neoplasm of the posterior mediastinum. In this case, we present a traumatic hemothorax as the initial presentation for a previously undiscovered mediastinal mass. The patient presented with shortness of breath and right-sided chest pain after being struck in the chest with a soccer ball. An operative exploration was pursued due to persistent hemothorax with hemodynamic instability despite resuscitation and adequate thoracostomy tube placement. The intraoperative etiology of bleeding was discovered to be traumatic fracture of a large hypervascular posterior mediastinal schwannoma. Surgical resection is the treatment of choice for these tumors. Specific serological markers do not exist for this tumor, and radiographic findings can be variable, so tissue diagnosis is of importance in differentiating benign from malignant schwannomas, as well as other posterior mediastinal tumors. However, most patients have excellent survival following complete resection.